Field emission properties of SiO2-wrapped CNT field emitter - Lim, Yu Dian (2020)
Carbon nanotubes (CNTs) exhibit unstable field emission (FE) behavior with low reliability due to uneven heights of as-grown CNTs. It has been reported that a mechanically polished SiO2-wrapped CNT field emitter gives consistent FE performance due to its uniform CNT heights. However, there are still a lack of studies on the comparison between the FE properties of freestanding and SiO2-wrapped CNTs. In this study, we have performed a comparative study on the FE properties of freestanding and SiO2-wrapped CNT field emitters. From the FE measurements, freestanding CNT field emitter requires lower applied voltage of 5.5 V μm-1 to achieve FE current density of 22 mA cm-2; whereas SiO2-wrapped field emitter requires 8.5 V μm-1 to achieve the same current density. This can be attributed to the lower CNT tip electric field of CNTs embedded in SiO2, as obtained from the electric field simulation. Nevertheless, SiO2-wrapped CNTs show higher consistency in FE current than freestanding CNTs. Under repeated FE measurement, SiO2-wrapped CNT field emitter achieves consistent FE behavior from the 1st voltage sweep, whereas freestanding field emitter only achieved consistent FE performance after 3rd voltage sweep. At the same time, SiO2-wrapped CNTs exhibit better emission stability than freestanding CNTs over 4000 s continuous emission.